Keurig : from David to Goliath : the challenge of gaining and maintaining marketplace leadership - Anderson, Eric T.; Anderson, Elizabeth ([London] : SAGE, 2016)
From 2002 to 2011, coffee-machine manufacturer Keurig had grown from a privately held company with just over $20 million in revenues to become a wholly owned subsidiary of Green Mountain Coffee Roasters, a publicly traded company with net revenues of $1.36 billion. This case examines the rapid rise of Keurig.
Originally Published in: Anderson, E. T., & Anderson, E. (2012). Keurig: From David to Goliath: The Challenge of Gaining and Maintaining Marketplace Leadership. 5-411-751. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Green Mountain Coffee Roasters, Inc; Marketing -- Management -- Case studies; Competition -- Case studies; Strategic planning -- Case studies; Corporations -- Growth -- Case studies